Embryonic Alcohol Exposure Impairs the Dopaminergic System and Social Behavioral Responses in Adult Zebrafish - Fernandes, Yohaan (Int J Neuropsychopharmacol, 2015)
BACKGROUND: The zebrafish is a powerful neurobehavioral genetics tool with which complex human brain disorders including alcohol abuse and fetal alcohol spectrum disorders may be modeled and investigated. Zebrafish innately form social groups called shoals. Previously, it has been demonstrated that a single bath exposure (24 hours postfertilization) to low doses of alcohol (0, 0.25, 0.50, 0.75, and 1% vol/vol) for a short duration (2 hours) leads to impaired group forming, or shoaling, in adult zebrafish. METHODS: In the current study, we immersed zebrafish eggs in a low concentration of alcohol (0.5% or 1% vol/vol) for 2 hours at 24 hours postfertilization and let the fish grow and reach adulthood. In addition to quantifying the behavioral response of the adult fish to an animated shoal, we also measured the amount of dopamine and its metabolite 3,4-dihydroxyphenylacetic acid from whole brain extracts of these fish using high-pressure liquid chromatograph. RESULTS: Here we confirm that embryonic alcohol exposure makes adult zebrafish increase their distance from the shoal stimulus in a dose-dependent manner. We also show that the shoal stimulus increases the amount of dopamine and 3,4-dihydroxyphenylacetic acid in the brain of control zebrafish but not in fish previously exposed to alcohol during their embryonic development. CONCLUSIONS: We speculate that one of the mechanisms that may explain the embryonic alcohol-induced impaired shoaling response in zebrafish is dysfunction of reward mechanisms subserved by the dopaminergic system.